3+3•[3+3•(3-3:3)]:9:3
Răspunsuri la întrebare
Răspuns de
2
3 + 3 × [ 3 + 3 × ( 3 - 3 : 3 ) ] : 9 : 3 =
3 + 3 × [ 3 + 3 × ( 3 - 1 ) ] : 9 : 3 =
3 + 3 × ( 3 + 3 × 2 ) : 9 : 3 =
3 + 3 × ( 3 + 6 ) : 9 : 3 =
3 + 3 × 9 : 9 : 3 =
3 + 27 : 9 : 3 =
3 + 3 : 3 =
3 + 1 =
= 4
3 + 3 × [ 3 + 3 × ( 3 - 1 ) ] : 9 : 3 =
3 + 3 × ( 3 + 3 × 2 ) : 9 : 3 =
3 + 3 × ( 3 + 6 ) : 9 : 3 =
3 + 3 × 9 : 9 : 3 =
3 + 27 : 9 : 3 =
3 + 3 : 3 =
3 + 1 =
= 4
Răspuns de
5
3 + 3 × [3 + 3 × (3 - 3 : 3)] : 9 : 3 =
3 + 3 × [3 + 3 × (3 - 1)] : 9 : 3 =
3 + 3 × (3 + 3 × 2) : 9 : 3 =
3 + 3 × (3 + 6) : 9 : 3 =
3 + 3 × 9 : 9 : 3 =
3 + 27 : 9 : 3 =
3 + 3 : 3 =
3 + 1 = 4
3 + 3 × [3 + 3 × (3 - 1)] : 9 : 3 =
3 + 3 × (3 + 3 × 2) : 9 : 3 =
3 + 3 × (3 + 6) : 9 : 3 =
3 + 3 × 9 : 9 : 3 =
3 + 27 : 9 : 3 =
3 + 3 : 3 =
3 + 1 = 4
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Geografie,
9 ani în urmă